2019
DOI: 10.1039/c9ce01332f
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-to-crystal transformation and linker exchange in Cd(ii) coordination polymers based on flexible bis-pyridyl-bis-amide and 1,4-naphthalenedicarboxylate

Abstract: Solvothermal reactions of Cd(ii) salts and naphthalene-1,4-dicarboxylic acid with bis(N-pyrid-3-ylmethyl)adipoamide and bis(N-pyrid-3-ylmethyl)suberoamide yield three Cd(ii) coordination polymers that undergo reversible crystal-to-crystal transformation and linker exchange.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The structural transformation of complexes can lead to different properties, such as colour, morphology, adsorption, chirality, luminescence and magnetism. [1][2][3][4][5][6][7][8][9][10][11][12][13] The potential application value brought by the diversity of complex structures has attracted more and more attention. 14 The structural transformation is usually characterized by small changes in the number and order of uncoordinated molecules at the molecular level, such as the addition and removal of solvents or guest molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The structural transformation of complexes can lead to different properties, such as colour, morphology, adsorption, chirality, luminescence and magnetism. [1][2][3][4][5][6][7][8][9][10][11][12][13] The potential application value brought by the diversity of complex structures has attracted more and more attention. 14 The structural transformation is usually characterized by small changes in the number and order of uncoordinated molecules at the molecular level, such as the addition and removal of solvents or guest molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Noticeably, the L 1 , L 2 , and L 3 ligands in 1 – 8 bridge two metal ions through two pyridyl nitrogen atoms, while the L 3 ligand of 9 bridges four metal ions through two pyridyl nitrogen atoms and two amide oxygen atoms. The bpba ligands that bridge four metal ions are rare and can be found for the bis(N-pyrid-3-ylmethyl)suberoamide (L) in {[Cd(L)(1,4-NDC)]·2H 2 O} n (1,4-H 2 NDC = naphthalene-1,4-dicarboxylic acid) and {[Cd 2 (L)(1,4-NDC) 2 ]·3H 2 O} n [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Polycarboxylate ligands that show diverse coordination modes involving chelating and bridging are important in the organization of CPs in a mixed system . We have been committing to the design and synthesis of bis-pyridyl-bis-amide (bpba)-based CPs, and several of them thus prepared with , or without the involvement of dicarboxylate ligands exhibited structural transformations. We have shown that CPs composed of N , N ′-di-3-pyridylsuberoamide and 1,4-naphthalenedicarboxylate (1,4-NDC 2– ) exhibit irreversible structural transformation due to the weak coordination ability of the ethanol molecule and the variation of bonding modes of the 1,4-NDC 2– ligands, while reorientation of amide oxygen atoms was proposed for the reversible structural transformations in the CPs containing bis­( N -pyrid-3-ylmethyl)­suberoamide and 1,4-NDC 2– …”
Section: Introductionmentioning
confidence: 99%
“…We have shown that CPs composed of N,N′-di-3-pyridylsuberoamide and 1,4naphthalenedicarboxylate (1,4-NDC 2− ) exhibit irreversible structural transformation due to the weak coordination ability of the ethanol molecule and the variation of bonding modes of the 1,4-NDC 2− ligands, 13 while reorientation of amide oxygen atoms was proposed for the reversible structural transformations in the CPs containing bis(N-pyrid-3-ylmethyl)suberoamide and 1,4-NDC 2− . 14 The tetracarboxylic acids that may display variable coordination modes have been widely used to prepare diverse CPs. 20−23 Therefore, the tetracarboxylate ligands are capable for the building of multidimensional architectures, and a variety of coordination modes adopted by the tetracarboxylate may govern the possible structural transformations among the CPs thus prepared.…”
Section: ■ Introductionmentioning
confidence: 99%